PPTC7 acts as an essential co-factor of the SCFFBXL4 ubiquitin ligase complex to restrict BNIP3/3L-dependent mitophagy - Xiayun Xu; Yingji Chen; Siqi Fei; Xinyue Jiang; Xiaoting Zhou; Yimeng Xue; Yao Li; Shi-Min Zhao; Yan Huang; Chenji Wang (Cell Death and Disease)
Abstract Mitophagy is a selective process that targets the damaged, dysfunctional, or superfluous mitochondria for degradation through autophagy. The SCFFBXL4 E3 ubiquitin ligase complex suppresses basal mitophagy by targeting BNIP3 and BNIP3L, two key mitophagy cargo receptors, for ubiquitin-proteasomal degradation. FBXL4 loss-of-function mutations lead to excessive BNIP3/3L-dependent mitophagy, thereby causing a devastating multi-system disorder called mitochondrial DNA depletion syndrome, type 13 (MTDPS13). PPTC7, a mitochondrial matrix phosphatase, is essential for proper mitochondrial function and biogenesis. Here, we show that a proportion of PPTC7 is located on the outer mitochondrial membrane, where it interacts with FBXL4 and BNIP3/3L. PPTC7 decreases BNIP3/3L protein stability in a protein phosphatase activity-independent manner. Using in vitro cell culture and Pptc7 knockout mouse model, we demonstrate that PPTC7 deficiency activates high levels of basal mitophagy in a BNIP3/3L-dependent manner. Mechanistically, PPTC7 facilitates SCFFBXL4-mediated ubiquitin-proteasomal degradation of BNIP3/3L. Overall, these findings establish PPTC7 as an essential co-factor of the SCFFBXL4 complex and a suppressor of BNIP3/3L-dependent mitophagy.